Aktuelle Studienlage zum Bauchdeckenverschluss: klassische Nahttechniken = Current standards of abdominal wall closure techniques : conventional suture techniques - Heger, Patrick; Pianka, Frank; Diener, Markus K.; Mihaljevic, André Leopold (Der Chirurg, 2016)
BackgroundThe most frequent complications following midline abdominal laparotomy include incisional hernias, which develop in 10-15 % of patients and surgical site infections in 15-25 % of cases; however, the risk of these complications can be reduced by the surgical technique and the use of special suture materials. In 2010, the INLINE meta-analysis performed by the Study Centre of the German Society of Surgery (SDGC) revealed that a continuous suture technique using slowly absorbable suture material resulted in the lowest risk of developing postoperative incisional hernia after elective midline laparotomy.ObjectiveThe aim of this study was to perform a systematic literature search to identify all randomized controlled trials (RCTs) that have been published since 2010 concerning conventional abdominal wall closure in order to update the 2010 INLINE meta-analysis and summarize current evidence.Material and methodsOn 28 January 2016, a systematic literature search was performed in MEDLINE and the Cochrane Central Register of Controlled Trials (CENTRAL). All RCTs dealing with abdominal wall closure after midline laparotomy were identified and included for further analysis.ResultsSince 2010 a total of 9 RCTs comparing different techniques of abdominal wall closure have been published. Three monocentric RCTs comparing different suture materials, showed no significant differences to the INLINE meta-analysis regarding incisional hernia development; therefore, slowly absorbable sutures using a continuous suture technique are still recommended for abdominal wall closure in elective cases. Furthermore, six RCTs were identified which investigated antimicrobial suture materials but failed to show an overall advantage for Triclosan-coated suture material with respect to surgical site infections.ConclusionCurrent evidence shows that slowly absorbable monofilament suture material using a continuous suture technique provides the best results with regard to incisional hernia rates after elective midline laparotomy. Triclosan-coated sutures cannot be recommended as a standard suture material as they failed to reduce surgical site infections. For emergency laparotomies no evidence exists to recommend a specific kind of suture technique or a special suture material.
Gesehen am 14.02.2018